α1-3/4 fucosylation at Asn 241 of β-haptoglobin is a novel marker for colon cancer: A combinatorial approach for development of glycan biomarkers - Park, Seung-Yeol; Lee, Sung-Hyeon; Kawasaki, Nana; Itoh, Satsuki; Kang, Keunsoo; Hee Ryu, Soo; Hashii, Noritaka; Kim, Jin-Man; Kim, Ji-Yeon; Hoe Kim, Jung (International journal of cancer, 2012)
Aberrant glycosylation has been observed in many types of cancer, but the mechanism of glycosylation change is still poorly understood. To elucidate relationships between glycosylation and colon cancer progression, we analyzed glycosylation status of β‐haptoglobin (β‐Hp) obtained from 46 cancer patients, 14 inflammatory bowel disease patients and 38 normal subjects. Aleuria aurantia lectin reactivity with cancer β‐Hp was much higher than in the other two study groups. These results were confirmed by lectin blotting and microarray assay using other lectins directed to fucosyl residues. Levels of such glycans were correlated with stage of colon cancer progression. Reactivity with fucosylated glycans was eliminated by treatment with α1‐3/4 fucosidase but not α1‐6 fucosidase, indicating that enhanced lectin reactivity with the fucose moiety of colon cancer β‐Hp is due to Fucα1‐3/4GlcNAc. Moreover, site‐specific glycan occupancy was determined by sequential LC/MS analysis. Mass spectrometric analysis showed that fucosylation of β‐Hp was higher in colon cancer patients than in other subjects. In particular, fucosylation at Asn 241 of β‐Hp in sera of colon cancer patients was clearly higher than in the other groups, and the ratio of fucosylated glycopeptides containing Asn 241 decreased greatly after treatment with α1‐3/4 fucosidase. In conclusion, the level of α1‐3/4 fucosyl epitope at Asn 241 of β‐Hp is potentially useful as a novel marker for colon cancer.